Septin Cytoskeleton Dynamics on B cell Activation and Antibody Responses - Auvinen, Silja (My University, 2026)
B cells perform a vital role in keeping the host organism safe against pathogens by recognizing exogenous and endogenous antigens via their B cell receptors (BCRs) and producing antibodies against said antigens. After an antigen binds to a BCR, the BCR-antigen complex is internalized and processed further. Several known mechanisms and players such as the actin cytoskeleton and endocytosis help explain how the BCR-antigen complex is internalized and processed; however, the whole picture remains unclear. In this study we focused on the septin cytoskeleton, particularly on the role of septin-7, and how its function affects B cells’ activation and antibody responses. To infer the possible role of septin cytoskeleton in B cell activation, forchlorfenuron (FCF) was used to inhibit the dynamics of septin filaments in antigen activated mouse lymphoma cells. These cells were then probed for phosphorylated proteins to examine whether the septin cytoskeleton plays a role in cell signalling. To examine organelle dynamics septin cytoskeleton dynamics were again inhibited with FCF after antigen activation to examine how the septin filaments associate with other cytoskeletal components, notably the microtubules. To look at humoral responses, mice that were either septin-7 wild type (WT) or conditional septin-7 knock-out in B cells (cKO) were immunized with an immunogen that would elicit T cell help. After immunization, the changes in the serum antibody levels were tracked. This study contains preliminary results showing that inhibition of septin cytoskeleton dynamics leads to a decrease on BCR activation upon antigen stimulation, which is reversible upon washing off the inhibitor FCF. At another level, we confirm that septin inhibition impairs B cells’ ability to spread over an antigen- coated surface, thus making it difficult for the B cells to form immune synapses. Furthermore, we can tentatively verify that in in vivo septin-7 conditional knockout mouse model the T-dependent response in B cells is diminished.
Keywords: septins, cytoskeleton, B cells, immunology, antibodies